Assessment of Level of Risk in Decision-Making in Terms of Career Exploitation - Semenov, Aleksandr Sergeevich; Kuznetcov, Vladimir Sergeevich (International Journal of Economics and Financial Issues, 2015)
When designing career plots the raw data are stochastic in nature. From the results of the determination of these initial data depends not only the final result of the design or evaluation, but also the feasibility of the development of the field. While there are significant errors associated with the probabilistic nature of the source data and measurement errors and errors of calculations. Risk assessment is an integral part of project documentation. The project decision-making occurs under conditions of uncertainty and risk. To minimize uncertainty, it is first necessary to identify the area of potential risk, to determine the probability of its occurrence and the potential consequences. If adverse effects cannot be excluded, a more complete understanding of the problem and contributes more mindful response to the potential risk. Analysis of the traditional approaches to designing open pits in the face of uncertainty of input data, revealed that used design methods do not account for the risk that entails the adoption and implementation of inefficient design solutions. Risk assessment is made in the design process and includes qualitative and quantitative analysis. If the evaluation of the project will be adopted for implementation, the mining companies are already faced with some problems of risk management. According to the results of the project accumulates statistics, which allows you to more accurately identify risks and work with them. When the uncertainty of the project is too high, then it can be sent back for revision, then again, there must be a risk assessment. Keywords: open-pit mine, a working platform, risk, design, reliability, probability, source data JEL Classifications: J54, M14